In der Welt der Vielen: Arendts sokratisches Ethos weltbürgerlicher Existenz im Lichte der Pluralität - Heller, Till (HannahArendt.net, 2023)
The starting point of this contribution is Arendt’s political phenomenology of a plural world, which as such is never simply pre-given, but is first created and kept open in interpersonal action and interaction. In this way, a public space of appearance of human plurality is constituted and actualized, in which citizens can negotiate their affairs in a non-violent manner as free among equals and act in a self-responsible manner, following the model of the polis. This redefinition of the political from the practical execution of active life has far-reaching consequences for the question of cosmopolitanism, which Arendt only touched upon, and which is opened up anew in particular by recourse to her reflections on the Socratic mode of thinking and existence. Starting from the constitutive ‘in-between’ of an original plurality of approaches to the world, Arendt – so the thesis – implicitly unfolds a Socratic ethos of cosmopolitan existence corresponding to her phenomenology of the political, which is articulated as ‘concern for the world’ in judgment, speech and action. This expresses a specific way of being-in-the-world together, characterized by a virtuousness paradigmatically embodied by Socrates, as well as mobility between thought and action, theory and practice, which calls us to render an account to ourselves and to others in harmony with the logos and under the umbrella of the sensus communis.